2006
DOI: 10.1111/j.1460-9568.2006.05170.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation rearing induces recognition memory deficits accompanied by cytoskeletal alterations in rat hippocampus

Abstract: Social isolation from weaning affects hippocampal structure and function in the rat. The intrinsic dynamic instability of the cytoskeletal microtubular system is essential for neuronal development and organization. Accordingly, the present paper investigated the effects of social isolation on hippocampal levels of alpha-tubulin isoforms associated with microtubule dynamics, the dendritic marker MAP-2 and alterations in locomotor activity and recognition memory. Male Lister Hooded rats (postnatal day 25-28) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
130
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(149 citation statements)
references
References 66 publications
13
130
1
5
Order By: Relevance
“…Our findings that chronic isolation significantly impaired contextual fear conditioning and spatial memory, but not auditory-cued fear conditioning or nonspatial performance in the water maze are consistent with previous reports that either acute (Barrientos et al, 2003) or chronic (Kogan et al, 2000;Bianchi et al, 2006) isolation markedly impaired hippocampal-dependent memory, but not memory that does not depend on hippocampal functioning. Previous studies on the effects of chronic stress on hippocampal neurogenesis demonstrated decreased cell proliferation in the dentate gyrus following chronic isolation (Dong et al, 2004), as well as several other chronic stressors (Simon et al, 2005; Lee et al, 2006;.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings that chronic isolation significantly impaired contextual fear conditioning and spatial memory, but not auditory-cued fear conditioning or nonspatial performance in the water maze are consistent with previous reports that either acute (Barrientos et al, 2003) or chronic (Kogan et al, 2000;Bianchi et al, 2006) isolation markedly impaired hippocampal-dependent memory, but not memory that does not depend on hippocampal functioning. Previous studies on the effects of chronic stress on hippocampal neurogenesis demonstrated decreased cell proliferation in the dentate gyrus following chronic isolation (Dong et al, 2004), as well as several other chronic stressors (Simon et al, 2005; Lee et al, 2006;.…”
Section: Discussionsupporting
confidence: 93%
“…The NOR task was performed as described (5). An inter-trial interval (ITI) of 2 h was used between the familiarization and the choice trial.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these circuits also appear to be capable of integrating over much longer time scales (i.e., days to months), thus allowing the functionality of these structures to be shaped by relatively subtle changes in the environment. Consistent with this idea, in animal studies, alterations in the external environment which enhance sensory stimulation (i.e., environmental enrichment; EE), or conversely, environmental conditions that deprive the animal of stimuli for many weeks, have been found to profoundly affect/shape cognitive capacity (van Praag et al 2000;Bruel-Jungerman et al 2005;Bianchi et al 2006). At a cellular level, EE triggers an increase in the generation and integration of adult-born neurons into the granule cell layer (GCL) of the hippocampus and increases dendritic branching complexity and synapse formation in excitatory neurons of the hippocampus (Kempermann et al 1997(Kempermann et al , 1998van Praag et al 2000;Faherty et al 2003).…”
mentioning
confidence: 86%
“…At a cellular level, EE triggers an increase in the generation and integration of adult-born neurons into the granule cell layer (GCL) of the hippocampus and increases dendritic branching complexity and synapse formation in excitatory neurons of the hippocampus (Kempermann et al 1997(Kempermann et al , 1998van Praag et al 2000;Faherty et al 2003). Further, reduced sensory stimulation leads to a decrease in progenitor proliferation and dendrite branch patterns, which likely results in the wellcharacterized increase in depression and reduced cognitive capacity (Silva-Gomez et al 2003;Bianchi et al 2006;Ibi et al 2008). Importantly, retrospective analysis of humans exposed to psychosocial or behavioral enrichment appears to support the findings of animal studies (Cotman and Berchtold 2002;Agrigoroaei and Lachman 2011;Erickson et al 2011).…”
mentioning
confidence: 99%